Etringite / nano hydrated calcium silicate early strength agent as well as preparation method and application thereof
Through the composite early strength agent of ettringite and nano-hydrated calcium silicate, the synergistic effect of ettringite and nano-hydrated calcium silicate of different sizes is solved by using the synergistic effect of ettringite in silicate-based cement. The restricted problem significantly improves the early mechanical strength of the cement and optimizes the overall performance of the cement slurry.
Patent Information
- Application Number
- CN202411510777.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the early strength effect of ettringite seeds in silicate cement is limited, and there is little research on its geometric morphology and particle size regulation, which affects the improvement of the early mechanical strength of cement.
Through the combined use of appropriate size ettringite and nano-hydrated calcium silicate, three ettringite seeds of different sizes were prepared, and the solution method was optimized by combining specific proportions, combining with the use of polycarboxylic acid water reducing agents. The synthesis process forms a uniform ettringite aqueous dispersion as an early strength agent to improve the early mechanical strength of silicate-based cement.
It significantly improves the early mechanical strength of silicate-based cement, shortens the initial settling time, and improves the overall performance of the cement slurry without damaging the later strength.
Smart Images

Figure CN119263682A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete admixtures, and more specifically to an ettringite / nano hydrated calcium silicate early strength agent and a preparation method and application thereof. Background Art
[0002] Seed (nucleus) early strength agent is one of the most effective technical means to achieve early strength and high strength for cement-based composite materials, especially suitable for special working conditions such as winter construction, emergency repair and construction, and jet grouting. The main working principle of seed early strength agent is to provide additional nucleation sites for cement hydration, reduce the nucleation barrier of cement hydration reaction, and thus accelerate the cement hydration process; in addition, nanoparticles can also fill the pore structure in hardened cement paste, reduce porosity and achieve pore refinement, further improve the cement slurry structure, and effectively improve the early mechanical strength and durability of cement concrete.
[0003] For the silicate series cement widely used in engineering practice at home and abroad, the seed-type early strength agent currently in the research and development stage is basically based on calcium silicate hydrate CSH as the functional component, and the development and application promotion of ettringite seeds are extremely scarce. Patent ZL201610785468.5 and patent application 202110570286.7 respectively disclose a method for preparing submicron ettringite and nano ettringite nuclei, but the application of seed early strength agent is limited to sulphoaluminate cement and its composite materials. In 2023, the applicant team disclosed a solution method for synthesizing calcium sulfonate and its enhancement effect on the early strength of ordinary Portland cement (research paper: Liaoning Chemical Industry, 2023, 53(6): 915-918). However, due to the limited content of clinker mineral C3A in ordinary cement PO 42.5, generally not exceeding 8%, the early strength effect of cement formed by calcium sulfonate seeds is also affected to a certain extent; in 2024, the applicant team further introduced synthetic calcium sulfonate and nano-hydrated calcium silicate into silicate cement paste to explore the effect of composite seeds on the early mechanical strength of cement, and achieved positive results, further improving the 1d and 3d mechanical strength of ordinary cement paste (research paper: China Powder Technology, 2024, 30(4): 62-68).
[0004] Existing research results show that calcium sulfonate seeds can not only act on sulphoaluminate cement, but also have a certain early strength effect on silicate cement. However, due to the low proportion of calcium sulfonate in the early hydration products of silicate cement, the effect of calcium sulfonate seeds is limited; if used in combination with hydrated calcium silicate seeds, the early strength effect can be greatly improved. It should be pointed out that the current research and development work mainly examines the cement early strength effect of calcium sulfonate and its composite seeds from the perspective of dosage, but the effective control method of the seed geometry, especially the particle size, and the research on its effect have not been published. Summary of the invention
[0005] In view of the deficiencies of the above prior art, one of the objects of the present invention is to provide an ettringite / nano-calcium silicate hydrate early strength agent, which is prepared by compounding ettringite seeds of suitable sizes in a specific proportion and then combining them with nano-calcium silicate hydrate seeds to form composite seeds, which can be used as an early strength agent to significantly improve the mechanical properties of silicate cement.
[0006] The above object of the present invention is achieved through the following technical solutions: A ettringite / nano calcium silicate hydrate early strength agent, the early strength agent comprises ettringite and nano calcium silicate hydrate, the ettringite is in the shape of short rods, including three sizes, and the distribution of each size and the percentage of the total mass of the ettringite are: Diameter 40~50nm, accounting for 40%~80%; Diameter 70~90nm, accounting for 10%~30%; The diameter is 120~150nm, accounting for 10%~30%.
[0007] The test results show that calcium sulfonate seeds also have a certain strengthening effect on silicate cement. However, due to the limited content of clinker mineral C3A in silicate cement, the calcium sulfonate formed by the reaction is also concentrated in the early stage of hydration, resulting in the calcium sulfonate seeds mainly playing a role in the properties of silicate cement such as setting time and early strength. However, in the case of using nano-hydrated calcium silicate seeds, calcium sulfonate can not only play its own seed role, accelerate early hydration, and promote the formation of calcium sulfonate hydration products, but also change the morphology of calcium sulfonate hydration products (complete and coarse crystals). The formed coating has a large porosity and high permeability coefficient, which is conducive to the early end of the cement hydration induction period and shortening the initial setting time; while the use of nano-hydrated calcium silicate has the effect of accelerating the hydration of C3S and promoting the formation of a large amount of CSH. Under the synergistic effect of the two seeds, the early mechanical strength of silicate cement paste can be significantly improved.
[0008] On the other hand, the early strength effect of cement of ettringite seed crystals is directly related to its grain size: the smaller the grain size, the faster the hydration speed and the higher the early strength. However, if the grains are too fine, too much product will be formed in a short time, which will lead to the generation of crystallization stress, and then the later strength increase will be limited or even the strength will be reduced. The present invention can further enhance the early strength effect of the composite seed crystals by combining ettringite of suitable size in a specific ratio on the basis of composite hydrated calcium silicate and ettringite.
[0009] Preferably, the mass ratio of the ettringite to the nano-calcium silicate hydrate is 1:(8-17).
[0010] Preferably, the length of the ettringite is 0.8-2 mm.
[0011] Another object of the present invention is to provide a method for preparing the ettringite / nano calcium silicate hydrate early strength agent, comprising the following steps: S1. Prepared separately ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C containing ettringite; wherein the diameter of the ettringite in the ettringite aqueous dispersion A is 40 to 50 nm, the diameter of the ettringite in the ettringite aqueous dispersion B is 70 to 90 nm, and the diameter of the ettringite in the ettringite aqueous dispersion C is 120 to 150 nm; S2. The mass ratio of the functional component ettringite is (40 to 80): (10 to 30): (10 to 30) and the ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C are mixed to obtain an ettringite aqueous dispersion; S3. The nanometer calcium silicate hydrate aqueous dispersion and the ettringite aqueous dispersion are mixed in a mass ratio of the functional components calcium silicate hydrate and ettringite of 1:(8-17) to obtain the early strength agent.
[0012] Preferably, the preparation method of the ettringite aqueous dispersion A comprises the following steps: A1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of polycarboxylate water reducer in the mixed solution is 3wt%; A2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction vessel. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:2. A3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion A with an ettringite diameter of 40 to 50 nm is obtained.
[0013] Preferably, the preparation method of the ettringite aqueous dispersion B comprises the following steps: B1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of the polycarboxylate water reducer in the mixed solution is 2wt%; B2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction vessel. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:2. B3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion B with an ettringite diameter of 70 to 90 nm is obtained.
[0014] Preferably, the preparation method of the ettringite aqueous dispersion C comprises the following steps: C1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of the polycarboxylate water reducer in the mixed solution is 1wt%; C2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction container. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:2. C3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion C with an ettringite diameter of 120 to 150 nm is obtained.
[0015] The invention uses a polycarboxylate water-reducing agent as a crystal growth inhibitor of ettringite, and limits the growth rate of ettringite crystals, especially the growth of rod crystal diameter, by effectively adsorbing polycarboxylate molecules on new ettringite crystal embryos; when the amount of the polycarboxylate water-reducing agent is different and other reaction conditions are the same, ettringite seeds of different sizes can be obtained, and the dispersing effect of the polycarboxylate water-reducing agent is added to finally obtain a uniform and stable ettringite seed dispersion.
[0016] By controlling the dripping speed of the mixed solution, the calcium ions (Ca 2+ ) and hydroxide (OH - ) is 1:2. This allows the calcium salt, aluminum sulfate and the OH provided by the initiator to - The ion concentration always remains relatively stable, which is beneficial to the chemical reaction and ensures the consistency of the product morphology.
[0017] The morphology uniformity of the ettringite product synthesized by the existing solution method is poor. The present invention optimizes the process steps of synthesizing ettringite by the solution method, especially controls the input method and dripping speed of the raw materials, aiming to ensure that the ion concentration of the solution environment remains basically stable during the formation of ettringite, which helps to make the particle morphology of the ettringite product more uniform and consistent.
[0018] Preferably, the concentration of calcium salt in the mixed solution is 0.01-0.15 mol / L.
[0019] Preferably, the initiator is a sodium hydroxide aqueous solution and / or a potassium hydroxide aqueous solution, with a concentration of 1-10 mol / L and a dripping speed of 0.1-1.0 mL / min.
[0020] Preferably, the mass fraction of ettringite in ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C is 0.6wt%~3.0wt%, and the mass fraction of nano-hydrated calcium silicate in the nano-hydrated calcium silicate aqueous dispersion is 0.5wt%~3.0wt%.
[0021] Preferably, the calcium salt includes at least one of calcium nitrate, calcium chloride and calcium bicarbonate.
[0022] The present invention also provides application of the ettringite / nano calcium silicate hydrate early strength agent in silicate cement-based materials, wherein the dosage of the ettringite / nano calcium silicate hydrate early strength agent is 1wt%-5wt% of the cement mass.
[0023] Compared with the prior art, the present invention is beneficial in that: (1) The present invention uses calcium silicate hydrate and ettringite in combination, and under the synergistic effect of the two crystal seeds, the early mechanical strength of the silicate cement paste is significantly improved; and on the basis of the composite calcium silicate hydrate and ettringite, ettringite of suitable size is used to combine them in a specific ratio, thereby further enhancing the early strength effect of the composite crystal seeds.
[0024] (2) The present invention adjusts and optimizes the process steps of synthesizing calcium sulfonate crystals by the solution chemical method. By maintaining the stability of the ion concentration of the solution environment during the formation of calcium sulfonate, the uniformity of the morphology of the fine calcium sulfonate product is improved, thereby enhancing the effect of the calcium sulfonate early strength agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the ettringite seed crystal of the present invention; Figure 2 This is a SEM image of the ettringite product when no crystal growth inhibitor is used. DETAILED DESCRIPTION
[0026] The preparation method of the ettringite / nano calcium silicate hydrate early strength agent of the present invention comprises the following steps: S1. Prepared separately ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C containing ettringite; wherein the diameter of the ettringite in the ettringite aqueous dispersion A is 40 to 50 nm, the diameter of the ettringite in the ettringite aqueous dispersion B is 70 to 90 nm, and the diameter of the ettringite in the ettringite aqueous dispersion C is 120 to 150 nm; S2. The mass ratio of the functional component ettringite is (40 to 80): (10 to 30): (10 to 30) and the ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C are mixed to obtain an ettringite aqueous dispersion; S3. The nanometer calcium silicate hydrate aqueous dispersion and the ettringite aqueous dispersion are mixed in a mass ratio of the functional components calcium silicate hydrate and ettringite of 1:(8-17) to obtain the early strength agent.
[0027] The preparation method of the ettringite aqueous dispersion A comprises the following steps: A1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of polycarboxylate water reducer in the mixed solution is 3wt%; A2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction vessel. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:2. A3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion A with an ettringite diameter of 40 to 50 nm is obtained.
[0028] The preparation method of the ettringite aqueous dispersion B comprises the following steps: B1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of the polycarboxylate water reducer in the mixed solution is 2wt%; B2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction vessel. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:2. B3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion B with an ettringite diameter of 70 to 90 nm is obtained.
[0029] The preparation method of the ettringite aqueous dispersion C comprises the following steps: C1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of the polycarboxylate water reducer in the mixed solution is 1wt%; C2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction container. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:2. C3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion C with an ettringite diameter of 120 to 150 nm is obtained.
[0030] In the present invention, the concentration of calcium salt in the mixed solution is 0.01-0.15 mol / L, calcium salt can be calcium nitrate, calcium chloride, calcium bicarbonate, and the initiator can be sodium hydroxide or potassium hydroxide, which has little effect on the performance of the early strength agent. The concentration of the initiator is 1-10 mol / L, and the dripping speed is 0.1-1.0 mL / min.
[0031] In the present invention, the mass fraction of ettringite in ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C is 0.6wt%-3.0wt%, and the mass fraction of nano-hydrated calcium silicate in the nano-hydrated calcium silicate aqueous dispersion is 0.5wt%-3.0wt%.
[0032] As an example, the nano-calcium silicate hydrate aqueous dispersion in the following examples and comparative examples is the nano-calcium silicate hydrate suspension prepared in Example 2 of CN114477836A, and the mass fraction of the nano-calcium silicate hydrate in the suspension is about 3wt%.
[0033] In the following examples and comparative examples, the solid content of the polycarboxylate water-reducing agent is 38%, and it is produced by Shenyang Yilida Admixture Factory.
[0034] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0035] The preparation method of the ettringite / nano calcium silicate hydrate early strength agent of the present embodiment comprises the following steps: P1. Prepare an aqueous dispersion A of ettringite with a diameter of 40 to 50 nm, the specific steps are as follows: P11. Calcium nitrate, aluminum sulfate and polycarboxylate water reducer are dissolved in water to obtain a mixed solution; the concentration of calcium nitrate in the mixed solution is 0.10 mol / L, the molar ratio of calcium nitrate to aluminum sulfate is 6:1; the mass fraction of polycarboxylate water reducer in the mixed solution is 3%; P12. Take 100mL of the mixed solution and place it in a reaction container. Under the condition of high-speed shear at 3000rpm, drip a 1mol / L sodium hydroxide aqueous solution at a uniform speed of 0.2mL / min. When the pH value of the reactant reaches 10.5, quickly start the peristaltic pump to drip the remaining 400mL of the mixed solution. Control the dripping speed so that the calcium ions (Ca 2+ ) and hydroxide (OH - ) is in a molar ratio of 1:2; P13. After the mixed solution was dripped, the peristaltic pump was turned off, and the sodium hydroxide aqueous solution was continued to be dripped until the pH value of the reactant reached 13.0. The stirring condition was maintained for 10 minutes to obtain a uniform and stable calcium sulfonate aqueous dispersion A. The mass fraction of calcium sulfonate in the calcium sulfonate aqueous dispersion was 3wt%. The diameter of calcium sulfonate in the calcium sulfonate aqueous dispersion A was measured by Zeta potential method to be 40~50nm and 0.8~1.2mm in length.
[0036] P2. Prepare an aqueous dispersion B of calcium sulfonate with a diameter of 70-90 nm. The preparation method is basically the same as step P1, except that the mass fraction of the polycarboxylate water reducer in the mixed solution is 2%. The diameter of calcium sulfonate in the aqueous dispersion B of calcium sulfonate is 70-90 nm and the length is 1.0-1.5 mm measured by the Zeta potential method.
[0037] P3. Prepare an aqueous dispersion C of calcium sulfonate with a diameter of 120-150 nm. The preparation method is basically the same as step P1, except that the mass fraction of the polycarboxylate water reducer in the mixed solution is 1%. The diameter of the calcium sulfonate in the aqueous dispersion C of calcium sulfonate is 120-150 nm and the length is 1.0-2.0 mm measured by the Zeta potential method.
[0038] P4 The ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C were mixed in a weight ratio of 60:30:10 to obtain an ettringite aqueous dispersion; P5. The ettringite aqueous dispersion obtained in step P4 is mixed with the nano-calcium silicate hydrate aqueous dispersion in a weight ratio of 3:50 to obtain an ettringite / nano-calcium silicate hydrate early strength agent.
[0039] Figure 1 The SEM images of the ettringite seeds prepared in Example 1, wherein (a) is the SEM image of the ettringite seeds prepared in step P1, (b) is the SEM image of the ettringite seeds prepared in step P2, and (c) is the SEM image of the ettringite seeds prepared in step P3. It can be seen from the figure that three different sizes of ettringite seeds were obtained in this example. In the comparative test, without using the crystal growth inhibitor polycarboxylate water reducer, the diameter of the obtained ettringite rod-shaped crystals exceeded 200nm and the length also reached more than 2mm, as shown in FIG. Figure 2 . Example 2
[0040] The ettringite / nano-hydrated calcium silicate early strength agent of this embodiment is substantially the same as that of Embodiment 1, except that in step P4, the weight ratio of ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C is 80:10:10. Example 3
[0041] The ettringite / nano-hydrated calcium silicate early strength agent of this embodiment is substantially the same as that of Embodiment 1, except that in step P4, the weight ratio of ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C is 40:30:30. Example 4
[0042] The ettringite / nano-hydrated calcium silicate early strength agent of this embodiment is basically the same as that of Embodiment 1, except that the molar concentration of calcium nitrate in the mixed solution is 0.02 mol / L, the concentration of sodium hydroxide solution is 5 mol / L, the dripping speed is 0.4 mL / min, and the mass fraction of ettringite in the obtained ettringite aqueous dispersion is 0.6 wt %. Example 5
[0043] The ettringite / nano-calcium silicate hydrate early strength agent of this embodiment is substantially the same as that of Embodiment 1, except that the weight ratio of the ettringite aqueous dispersion to the nano-calcium silicate hydrate aqueous dispersion in step P5 is 3:30. Comparative Example 1
[0044] The ettringite / nano-hydrated calcium silicate early strength agent of this comparative example is substantially the same as that of Example 1, except that the ettringite aqueous dispersion of this comparative example contains only ettringite aqueous dispersion A, that is, the diameter of the ettringite of this comparative example is 40-50 nm. Comparative Example 2
[0045] The ettringite / nano-hydrated calcium silicate early strength agent of this comparative example is substantially the same as that of Example 1, except that the ettringite aqueous dispersion of this comparative example contains only the ettringite aqueous dispersion B, that is, the diameter of the ettringite of this comparative example is 70-90 nm. Comparative Example 3
[0046] The ettringite / nano-hydrated calcium silicate early strength agent of this comparative example is substantially the same as that of Example 1, except that the ettringite aqueous dispersion of this comparative example contains only ettringite aqueous dispersion C, that is, the diameter of the ettringite of this comparative example is 120-150 nm. Comparative Example 4
[0047] The ettringite / nano-hydrated calcium silicate early strength agent of this comparative example is basically the same as that of Example 1, except that steps P1 to P3 are as follows: P1. Prepare an aqueous dispersion A of ettringite with a diameter of 40 to 50 nm, the specific steps are as follows: P11. Calcium nitrate, aluminum sulfate and polycarboxylate water reducer are dissolved in water to obtain a mixed solution; the concentration of calcium nitrate in the mixed solution is 0.10 mol / L, the molar ratio of calcium nitrate to aluminum sulfate is 6:1; the mass fraction of polycarboxylate water reducer in the mixed solution is 3%; P12. Take 500mL of the mixed solution and place it in a reaction container. Under the condition of high-speed shear at 3000rpm, uniformly add a 1mol / L sodium hydroxide aqueous solution at a rate of 0.2mL / min. When the pH value of the reactant reaches 13.0, maintain stirring conditions for 10min to obtain a uniform and stable calcium aluminate aqueous dispersion A.
[0048] P2. Preparation of an aqueous dispersion B of ettringite having a diameter of 70 to 90 nm. The preparation method is substantially the same as step P1, except that the mass fraction of the polycarboxylate water-reducing agent in the mixed solution is 2%.
[0049] P3. Preparation of an aqueous dispersion C of ettringite having a diameter of 120 to 150 nm. The preparation method is substantially the same as step P1, except that the mass fraction of the polycarboxylate water-reducing agent in the mixed solution is 1%.
[0050] That is, compared with Example 1, in this comparative example, the mixed solution is added at one time when preparing ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C. Test example
[0051] The early strength agent prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 was added to the cement paste at a dosage of 5wt%, and the dosage was controlled based on the cement mass, and the blank group was the one without early strength agent. The well-stirred paste was poured into a 20 mm × 20 mm × 20 mm cubic mold, and demolded after standard curing for 24 hours. The compressive strength of the samples was tested, and the remaining samples were cured to the specified age, and then their compressive strength was tested. The test results are shown in Table 1. To ensure the comparability of the experimental results, the total water-cement ratio of all samples in the test was controlled to 0.36, and the amount of water reducer was controlled to 0.2% of the cement mass. The cement was P•O42.5 ordinary Portland cement.
[0052] Table 1 Compressive strength results of test blocks
[0053] It can be seen from the data in Table 1 that, compared with the blank, the early strength agent of the present invention can significantly improve the early mechanical strength of silicate cement and can effectively ensure the later strength of cement paste.
[0054] By comparing Comparative Examples 1 to 3, it can be found that as the amount of the growth inhibitor polycarboxylate water-reducing agent increases, the size of the ettringite seed crystals decreases, the early strength of the cement paste increases, but the later strength decreases.
[0055] By comparing Example 1 with Comparative Examples 1 to 3, it can be found that when the calcium sulfonate crystal seeds in the early strength agent have only a small particle size of 40 to 50 nm or 70 to 90 nm in diameter, the late (28d) strength change rate of the cement paste test block is significantly reduced; when the calcium sulfonate crystal seeds in the early strength agent have only a large particle size of 120 to 150 nm in diameter, the 1d, 3d and 28d strength change rates of the cement paste test block are between 140% and 150%, and the change range is limited. By comparing Example 1 with Comparative Example 4, it can be found that when the preparation method of the calcium sulfonate aqueous dispersion of the present invention is changed, the size of the calcium sulfonate crystal seed product obtained is too large and the morphology uniformity is poor, resulting in a significant decrease in the strength of the cement paste test block at each age.
[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A calcium sulfonate / nano calcium silicate hydrate early strength agent, characterized in that: The early strength agent includes ettringite and nano-hydrated calcium silicate. The ettringite is in the shape of short rods and includes three sizes. The distribution of each size and the percentage of the total mass of the ettringite are as follows: Diameter 40~50nm, accounting for 40%~80%; Diameter 70~90nm, accounting for 10%~30%; The diameter is 120~150nm, accounting for 10%~30%.
2. The ettringite / nano calcium silicate hydrate early strength agent according to claim 1, characterized in that: The mass ratio of the ettringite to the nano-calcium silicate hydrate is 1:(8-17).
3. The method for preparing the ettringite / nano calcium silicate hydrate early strength agent according to claim 1 or 2, characterized in that: The following steps are involved: S1. Prepared separately ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C containing ettringite; wherein the diameter of ettringite in the ettringite aqueous dispersion A is 40 to 50 nm, the diameter of ettringite in the ettringite aqueous dispersion B is 70 to 90 nm, and the diameter of ettringite in the ettringite aqueous dispersion C is 120 to 150 nm; S2. The mass ratio of the functional component ettringite is (40 to 80): (10 to 30): (10 to 30) and the ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C are mixed to obtain an ettringite aqueous dispersion; S3. The nanometer calcium silicate hydrate aqueous dispersion and the ettringite aqueous dispersion are mixed in a mass ratio of the functional components calcium silicate hydrate and ettringite of 1:(8-17) to obtain the early strength agent.
4. The method for preparing a calcium aluminate / nano calcium silicate hydrate early strength agent according to claim 3, characterized in that: The preparation method of the ettringite aqueous dispersion A comprises the following steps: A1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of polycarboxylate water reducer in the mixed solution is 3wt%; A2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction vessel. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:
2. A3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.
0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion A with an ettringite diameter of 40 to 50 nm is obtained.
5. The method for preparing a calcium aluminate / nano calcium silicate hydrate early strength agent according to claim 3, characterized in that: The preparation method of the ettringite aqueous dispersion B comprises the following steps: B1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of the polycarboxylate water reducer in the mixed solution is 2wt%; B2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction vessel. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:
2. B3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.
0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion B with an ettringite diameter of 70 to 90 nm is obtained.
6. The method for preparing the ettringite / nano calcium silicate hydrate early strength agent according to claim 3, characterized in that: The preparation method of the ettringite aqueous dispersion C comprises the following steps: C1. Dissolve calcium salt, aluminum sulfate and polycarboxylate water reducer in water to obtain a mixed solution; the mass fraction of the polycarboxylate water reducer in the mixed solution is 1wt%; C2. Take 1 / 5~1 / 3 of the volume of the mixed solution and place it in a reaction container. Add the initiator at a uniform rate while stirring. When the pH value of the reactant reaches 10.5, add the remaining mixed solution. Control the dripping speed of the mixed solution so that the molar ratio of calcium ions to hydroxide ions dripped per unit time is 1:
2. C3. After the mixed solution is dripped, the initiator is continued to be dripped until the pH value of the reactant reaches 13.
0. After stirring for 10 to 30 minutes, an ettringite aqueous dispersion C with an ettringite diameter of 120 to 150 nm is obtained.
7. The method for preparing the ettringite / nano calcium silicate hydrate early strength agent according to any one of claims 4 to 6, characterized in that: The initiator includes sodium hydroxide and / or potassium hydroxide.
8. The method for preparing the ettringite / nano calcium silicate hydrate early strength agent according to any one of claims 4 to 6, characterized in that: The concentration of calcium salt in the mixed solution is 0.01~0.15mol / L.
9. The method for preparing the ettringite / nano calcium silicate hydrate early strength agent according to any one of claims 3 to 6, characterized in that: The mass fraction of ettringite in the ettringite aqueous dispersion A, ettringite aqueous dispersion B and ettringite aqueous dispersion C is 0.6wt%-3.0wt%, and the mass fraction of nano-hydrated calcium silicate in the nano-hydrated calcium silicate aqueous dispersion is 0.5wt%-3.0wt%.
10. Use of ettringite / nano calcium silicate hydrate early strength agent prepared by the method according to any one of claims 3 to 6 in silicate cement-based materials, characterized in that: The dosage of the ettringite / nano-hydrated calcium silicate early strength agent is 1wt%-5wt% of the cement mass.
Citation Information
Patent Citations
A submicron-sized ettringite, its preparation method, and its application as an early-strength agent in cement-based materials.
CN106396449B
Preparation method of nano ettringite crystal nucleus early strength agent, obtained product and application
CN113213803A
Preparation method of controllable nano hydrated calcium silicate early strength agent, nano hydrated calcium silicate early strength agent and application of nano hydrated calcium silicate early strength agent
CN114477836A
Cited By
Anti-carbonization sulphoaluminate cement repair mortar and preparation method thereof
CN121494469A
A carbonation-resistant sulfoaluminate cement repair mortar and its preparation method
CN121494469B
Super sulfate cement concrete based on construction waste aggregate and mineral and preparation method thereof
CN122277199A